The estimation of Poisson's ratio by time-averaging and Cornu's method for isotropic beams. (15th April 2023) - Luceadams, Matthew J.; Steinzig, Mike; Abdelkefi, Abdessattar; Mascareñas, David
Abstract: Prior research suggests that direct static (e.g., uniaxial testing) and dynamic (e.g., ultrasonic wave propagation analysis) measurements differ in the estimation of Poisson's ratio because anisotropies and heterogeneities in the sample material affect the two types of tests differently. Even assuming isotropic and homogeneous material properties, prior research further suggests that discrepancies between static/dynamic test results will exist because the error of the diagnostic techniques for the measurand are inherently different. Finally, thermodynamic effects are not present in static tests but can significantly affect dynamic test results. Given the potential for all these variables to produce discrepancies, it would be helpful to have the measurement of Poisson's ratio obtainable from the same theory and experimental measurements by either static or dynamic testing methods. Our finite element calculations show that by combining time-averaged scanning digital holography with Cornu's method, it is theoretically possible to estimate the effective Poisson's ratio from the anticlastic contours at the antinode of the first out-of-plane bending mode shape. This is true regardless of frequency and therefore applicable for both static and dynamic measurements. Our results show that the estimate of Poisson's ratio by Cornu's method using data from simulations of mode shapes approaches the true value of Poisson's ratio. In addition, our research suggests that beam geometry and boundary conditions are fundamental factors limiting the convergence of the estimate of Poisson's ratio to the true value of Poisson's ratio regardless of performing a static or dynamic test.